(untitled) (Research, Society and Development, 2023)
Gestational hypertensive syndromes (GHS) are the major cause of morbidity and mortality in pregnancy, and these are preventable. Thus, quality prenatal care and access to a qualified care service are imperative. They can be classified into chronic arterial hypertension, pre-eclampsia, gestational hypertension and pre-eclampsia superimposed on chronic hypertension. This article aims to analyze the profile of pregnant women who died from SHG, between 2012 and 2020 in Brazil. This is a retrospective epidemiological study, which uses data available at the Department of Informatics of the Unified Health System (DATASUS). From the analysis of the data collected, it is observed that socioeconomic conditions, quality of health care and regionality are essential for the analysis of maternal mortality in Brazil.